"A soldier of fortune": Henry Christophe, British loyalism, and the troubling question of political legitimacy. Issue 2 (3rd April 2019) - Forde, James
ABSTRACT: This article explores the multiple ways in which the legitimacy of Haiti's first and only king, Henry Christophe, was debated in Britain in the 1810s. Recent scholarship has led to a better understanding of how Christophe presented himself as a legitimate monarch in his efforts to gain diplomatic recognition of the Haitian state. However, exactly why British observers came to not only accept, but also write approvingly of the Haitian kingdom, is still unclear. This article argues that representations of Christophe and his court need to be read against a backdrop of British concerns regarding effective and legitimate governance in the early nineteenth century. In a range of newspapers, periodicals, and literature, Haiti's latest form of government became a central frame of reference in British debates concerning political legitimacy in the Atlantic world. In particular, at a time when post-revolutionary forms of power threatened conservative ideologies, British loyalists turned to the Haitian kingdom in their assertions of the superiority of Britain's monarchical government. In these conservative narratives, the figure of King Christophe was a fluid and often contradictory entity, and representations of him were formed to suit different assertions of what constituted political legitimacy. This article, therefore, highlights the wide-ranging frames of reference that British conservative observers looked to as they evaluated legitimacy in an age of revolution. These narratives also demonstrate how Haiti's different modes of government in its early years of independence influenced its attempts to gain recognition from the powers of the West, as well as how the Haitian state impacted – and was susceptible to – debates concerning sovereignty and the concept of good governance in the Atlantic world in the early nineteenth century.